Retrocaval ureter: a rare cause of urinary tract obstruction - Kulkarni, Narsinha Vamanrao; Sarda, Vikram R.; Gupta, Kartik Chandrakant (International Surgery Journal, 2019)
Retrocaval ureter is an uncommon cause of ureteric obstruction due to a rare congenital anomaly of inferior vena cava. We report a case of 23 year old male who presented with right flank pain and was diagnosed with ultrasound and intravenous urography. He underwent open retroperitoneal ureteroureterostomy.